Pengaruh Kompetensi Aparatur, Whistleblowing, dan Sistem Pengendalian Internal terhadap Pencegahan Fraud dalam Pengelolaan Dana Desa dengan Komitmen Organisasi sebagai variabel moderasi - Manalu, Lena Jessika (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This aim to determine the effect of Apparatus Competence, Whistleblowing, and Internal Control System on Fraud Prevention in Village Fund Management with Organizational Commitment as a Moderating Variable in Siantar District Simalungun Regency. This type of research is quantitative research using primary data. The population in this study was all village officials in the village in Siantar District with the sample determined using the purposive sampling method, totaling 85 respondents. The results of this research individually show that Apparatus Competence, Whistleblowing, and Internal Control System have a positive and significant effect on Fraud Prevention In Village Fund Management. Apparatus Competence, Whistleblowing, and Internal Control System simultaneously have a significant effect on Fraud Prevention In Village Fund Management. And Organizational Commitment as a moderating variable can strengthen the relation of Apparatus Competence, Whistleblowing, and Internal Control System on Fraud Prevention in Village Fund Management. Keywords: Apparatus Competence, Whistleblowing, Internal Control System, Fraud Prevention in Village Fund Management, Organizational Commit